Economic growth, financial development and trade openness in Nigeria: An application of the ARDL bound testing approach - Adedoyin Isola Lawal; Tony I. Nwanji; Abiola Asaleye; Victor Ahmed (Cogent Economics & Finance, 2016)
For over a decade now, various efforts have been put in place by various governments of the developing economies to promote economic growth, financial development and expand trade with mixed results. The ability of financial development and/or trade openness to influence economic growth in the developing economies has been a subject of hot debate and remains inconclusive. While a number of scholars are of the view that compelling cointegration exists among each of these constructs, another set of substantial authors have documented that economic growth, trade openness and financial development do evolve independent of each other. Drawing from four financial developments-growth nexus theories, this study used the ARDL bound estimation techniques to examine the existence of cointegration among economic growth, financial development and trade openness in Nigeria. We intend to know what policy instruments need to be manipulated so as to achieve economic growth and financial stability. Our results show that a two-way cointegration exists between economic growth and financial development, on the one hand, as well as between economic growth and trade openness, on the other hand. We therefore recommend that in order to achieve economic growth, policy-makers should pursue strong financial development and increase trade openness.
Keywords: C10; E01; F43; G00; O54; 330; economic growth; financial development; trade openness; ARDL; Nigeria